THE USE OF DIGITAL LEARNING OBJECTS IN THE NATURAL AND SOCIAL SCIENCE SUBJECT TO IMPROVE STUDENTS'S ECOLITERACY: Penggunaan Digital Learning Object Pada Mata Pelajaran IPAS Untuk Meningkatkan Ecoliteracy Siswa - Muhammad Raffy Maulana Gumelar; Laksmi Dewi; Ahmad Fajar Fadlillah (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
A person's concern for the environment (ecoliteracy) is crucial to instill from an early age to cultivate positive habits in environmental stewardship. To foster this concept, the education sector plays a strategic role through the introduction of subjects relevant to environmental issues. This study aims to investigate the use of digital learning objects (DLO) as a digital learning resource in Integrated Science and Social Studies (IPAS) subjects to enhance the ecoliteracy of sixth-grade students at SDN 195 Isola. In this research, ecoliteracy encompasses cognitive (head), affective (heart), and psychomotor (hands) learning outcomes. The research employed a pre-experimental method using a single research group with a One-Group Pretest Posttest Design for the head dimension and a One-Shot Case Study for the heart and hands dimensions. Sampling techniques involve purposive selection based on the characteristics of the sixth-grade students. Data collection employs various instruments, including tests, questionnaires, and performance assessments. The findings indicate that the utilization of digital learning objects in IPAS subjects leads to improvements in cognitive dimensions and positively influences affective and psychomotor dimensions. Enhanced visualization, increased user interaction, and improved knowledge retention contribute to cognitive growth. Active participation in environmental activities due to habituation supported by DLO is observed in the affective dimension. Additionally, the integration of DLO with simple recycling activities facilitates the connection between knowledge, skills, and real-life experiences in the psychomotor dimension. Based on the research findings, efforts to enhance student ecoliteracy need continuous updates, especially in the heart and hands dimensions.